2003
DOI: 10.1046/j.1469-7580.2003.00181.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the pelvic and penile urethra – relationship with the ducts of the sex accessory glands of the Mongolian gerbil (Meriones unguiculatus)

Abstract: The urethra is the main place of entry for sexually transmitted pathogens. However, there is little literature on the morphology of the urogenital system, principally the urethra and ducts of the sex accessory glands. The Mongolian gerbil is an insectivorous, herbivorous and monogamous rodent with nocturnal habits; it has been used successfully as a laboratory animal since the 1960s. Therefore, the objective of the present paper was to describe the structure and ultrastructure of the urethra and its relations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
1
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 13 publications
1
31
1
14
Order By: Relevance
“…In addition, the Mongolian gerbil (Meriones unguiculatus) has been recognized in some biomedical sciences, such as immunology (Nawa et al, 1994), physiology (Nolan et al, 1990), and morphology (Custódio et al, 2004;Pinheiro et al, 2003;Santos et al, 2003Santos et al, , 2006Corradi et al, 2004). More recently, gerbil has also been suggested as a suitable model for studies on mammalian aging (Pegorin de Campos et al, 2006).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the Mongolian gerbil (Meriones unguiculatus) has been recognized in some biomedical sciences, such as immunology (Nawa et al, 1994), physiology (Nolan et al, 1990), and morphology (Custódio et al, 2004;Pinheiro et al, 2003;Santos et al, 2003Santos et al, , 2006Corradi et al, 2004). More recently, gerbil has also been suggested as a suitable model for studies on mammalian aging (Pegorin de Campos et al, 2006).…”
mentioning
confidence: 99%
“…More recently, gerbil has also been suggested as a suitable model for studies on mammalian aging (Pegorin de Campos et al, 2006). Gerbil's prostate has compact lobes, somewhat similar to the human prostate, unlike rats and mice, which have distinct lobes (Pinheiro et al, 2003;Góes et al, 2006). Previous data from our laboratory has demonstrated that histological, histochemical, and ultrastructural features of the adult gerbil's prostate are comparable to the human prostate.…”
mentioning
confidence: 99%
“…As relações anatômicas das glândulas acessórias do aparelho genital masculino com a uretra também foram descritas por Pinheiro e cols. (7).…”
unclassified
“…Nos animais domésticos e alguns roedores, a uretra esta divida em duas regiões, a pélvica e peniana (esponjosa), que são revestidas por epitélio de transição (COOPER; HEBEL;STROMBERG, 1976;MENEZES, 2001;PINHEIRO et al, 2003).…”
Section: Espermatogêneseunclassified
“…A uretra peniana inicia no divertículo uretral localizado no bulbo do pênis, de formato de coração e simetria bilateral, encontra-se revestida pelo corpo esponjoso, ventral ao osso peniano e termina no óstio externo da uretra na parte distal do pênis, sendo constituída por epitélio estratificado colunar (PINHEIRO et al, 2003).…”
Section: Espermatogêneseunclassified